Layanan Bimbingan dan Konseling untuk Pelaku dan Korban Body Shaming - Taufik Agung Pranowo; Windi Tri Kusumastiti (Bulletin of Counseling and Psychotherapy, 2022)
The purpose of this research is to describe about Implementation of Guidance and Counseling Services provided by Guidance and Counseling Teachers to students for perpetrators and victims of body shaming. This type of research is qualitative research. Collecting data using the method of observation and interview methods. The instruments used for data collection are observation guidelines and interview guidelines. The place of research is at MTs Negeri 5 Sleman Yogyakarta. Sources of data in this study are Guidance and Counseling Teachers, Principals, Homeroom Teachers, and Students. The data analysis used is 1) data collection, 2) data reduction, 3) data presentation, and 4) drawing conclusions. The validity of data or trust in research results can be obtained by using source triangulation techniques. The results of this study found that Services for students’ victims and perpetrators of Body shaming are not included in the guidance and counseling program. Guidance and Counseling Teachers in the implementation of services for victims of Body shaming are mediation services, while for Body shaming perpetrators are individual counseling. The conclusion in this study is that the implementation of Guidance and Counseling Services for victims and perpetrators of body shaming at MTs N 5 Sleman Yogyakarta is that the guidance and counseling services provided are individual counseling given to perpetrators of body shaming and mediation services are used for victims of body shaming. Guidance and counseling services provided to perpetrators and victims of body shaming are still incidental.